Comparison of two different radioimmunoassays to measure 17-hydroxyprogesterone during treatment monitoring of children with congenital adrenal hyperplasia due to 21-hydroxylase deficiency - Kamrath, Clemens; Böhles, Hansjosef; Maser-Gluth, Christiane (Clinica chimica acta, 2011)
Background - Accurate measurement of 17-hydroxyprogesterone (17-OHP) concentrations is essential for the correct diagnosis and treatment management of children with congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency (21 OHD). - Methods - We analysed 102 serum samples from 15 children with known 21 OHD twice using two different 17-OHP assays. 17-OHP concentrations were measured by an in-house radioimmunoassay (RIA) after recovery-corrected extraction and chromatographic purification and by a commercially available RIA without extraction (Immunotech). - Results - The correlation coefficient for results of pairs of 17-OHP concentrations was 0.974. The median ratio (17-OHP concentration measured with the commercial assay/17-OHP concentration measured with the in-house assay) was 0.593 with a 95% confidence interval ranging from 0.258 to 1.370. The ratio was constant throughout the average 17-OHP concentrations ranging from 0.24 to 149.2nmol/L, as well as throughout the age range from 0.3 to 16.4years. - Conclusions - Despite good overall correlation, absolute 17-OHP concentrations differed dramatically. This could lead to misclassification of patients suspected for 21 OHD on the basis of the hormonal profile and to a reduced quality during treatment monitoring of patients with 21 OHD with the risk of under- and overtreatment.